The Inflammation-Based Glasgow Prognostic Score as a Prognostic Factor in Patients with Intensive Cardiovascular Care Unit - Altay, Servet (Medicina (Kaunas), 2019)
Background: The Glasgow prognostic score (GPS), which is obtained from a combination of C-reactive protein (CRP) and serum albumin level, predicts poor prognoses in many cancer types. Systemic inflammation also plays an important role in pathogenesis of cardiovascular diseases. In this study, we aimed to investigate the effect of inflammation-based GPS on in-hospital and long-term outcomes in patients hospitalized in intensive cardiovascular care unit (ICCU). Methods: A total of 1004 consecutive patients admitted to ICCU were included in the study, and patients were divided into three groups based on albumin and CRP values as GPS 0, 1, and 2. Patients’ demographic, clinic, and laboratory findings were recorded. In-hospital and one-year mortality rates were compared between groups. Results: Mortality occurred in 109 (10.8%) patients in in-hospital period, 82 (8.1%) patients during follow-up period, and thus, cumulative mortality occurred in 191 (19.0%) patients. Patients with a high GPS score had a higher rate of comorbidities and represented increased inflammatory evidence. In the multivariate regression model there was independent association with in-hospital mortality in GPS 1 patients compared to GPS 0 patients (Odds ratio, (OR); 5.52, 95% CI: 1.2–16.91, p = 0.025) and in GPS 2 patients compared to GPS 0 patients (OR; 7.01, 95% CI: 1.39–35.15, p = 0.018). A higher GPS score was also associated with a prolonged ICCU and hospital stay, and increased re-hospitalization in the follow-up period. Conclusion: Inflammation based GPS is a practical tool in the prediction of worse prognosis both in in-hospital and one-year follow-up periods in ICCU patients.